COVID-19 breakthrough infection among vaccinated individuals: A cross-sectional study - Sushant S Chavan; Madhuri Suryawanshi; Vikrant Pagar; Sarika P Patil; Amol D Kinge (Asian Journal of Medical Sciences, 2022)
Background: A cross-sectional study was carried out in urban area. The primary outcome of the study was the proportion of breakthrough infection in vaccinated subjects, which was defined as any COVID-19 infection occurring ≥30 days after receiving both the doses of either of the vaccine(s). Aims and Objectives: The aims of this study were to determine prevalence of COVID-19 breakthrough infection among COVID 19 vaccinated patients, (1) to study demographic factors affecting breakthrough infection and (2) to compare the proportion of breakthrough infection among Covishield and Covaxin recipients. Materials and Methods: The subjects were selected by systematic random sample method from available vaccination record. A questionnaire was administered in local language containing demographic information and COVID-related information. Nasopharyngeal swab was taken by trained Interns with all necessary precautions, RT-PCR swab was labeled and sent to PCR laboratory in cold chain for testing. Results: A total 445 subjects were tested for COVID-19. Subjects included 290 (65.2%) males and 155 (34.8%) females. Maximum cases were from age group of 21–30 year (23.4%). The mean age was found to be 43 year. About 8.85% subjects test result came positive despite taking two doses of either COVID vaccine. Breakthrough infection was more among males than females. Covaxin recipient subjects showed marginally higher percentage of breakthrough infection (9.1%) than Covishield. Out of the 39 breakthrough infections, 16 subjects were having comorbidities. Maximum breakthrough infection was seen in subjects having diabetes mellitus and hypertension both and hypertension alone (1.6%). Conclusion: A prevalence of 8.8% of COVID-19 breakthrough infection was reported in our study among fully vaccinated subjects after 30 days of last vaccine dose. Males are at higher risk of getting infection. People with comorbidities are at higher risk of breakthrough infection and hospitalization.